2018
DOI: 10.3390/jmse6020051
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Fluid–Structure Interaction Computations of Flexible Composite Propellers in Open Water Conditions Using BEM-FEM and RANS-FEM Methods

Abstract: In the past several decades, many papers have been published on fluid-structure coupled calculations to analyse the hydro-elastic response of flexible (composite) propellers. The flow is usually modelled either by the Navier-Stokes equations or as a potential flow, by assuming an irrotational flow. Phenomena as separation of the flow, flow transition, boundary layer build-up and vorticity dynamics are not captured in a non-viscous potential flow. Nevertheless, potential flow based methods have been shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…The stiffness contribution of the hub has been modelled by a full clamping of the propeller blade at the blade-hub interface. The models were discretised by quadratic solid elements using a 29 × 30 × 4 element distribution, meaning that 29, 30 and 4 elements are distributed in chord-wise, radial and through-thickness direction, respectively [13,27]. The added mass matrices have been computed from Equation (51) and diagonalised with a Hinton-Rock-Zienkiewicz lumping technique, which means that the diagonal entries of the full added mass matrix are scaled with the ratio of the sum of the entries that contribute to the motion in the same direction over the sum of the diagonal entries that contribute to the motion in that direction [7].…”
Section: Fluid Added Mass Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The stiffness contribution of the hub has been modelled by a full clamping of the propeller blade at the blade-hub interface. The models were discretised by quadratic solid elements using a 29 × 30 × 4 element distribution, meaning that 29, 30 and 4 elements are distributed in chord-wise, radial and through-thickness direction, respectively [13,27]. The added mass matrices have been computed from Equation (51) and diagonalised with a Hinton-Rock-Zienkiewicz lumping technique, which means that the diagonal entries of the full added mass matrix are scaled with the ratio of the sum of the entries that contribute to the motion in the same direction over the sum of the diagonal entries that contribute to the motion in that direction [7].…”
Section: Fluid Added Mass Validationmentioning
confidence: 99%
“…The fundamental difference between RANS and BEM is that, in the latter, a potential flow is assumed, meaning that phenomena as flow separation, flow transition, boundary layers and vorticity dynamics are not modelled. Results of validation studies on flexible propellers in open water conditions with BEM-FEM (finite element method) and RANS-FEM methods have been presented in [13]. Despite the limitations of a BEM and the complicated flow characteristics considered in that work, a fairly good estimate of the propeller hydro-elastic response was obtained with the BEM-FEM approach.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the accuracy of the computations should be verified and compared with results obtained in controlled scenarios, as, for example, during open water tests in a towing tank or cavitation tunnel. Despite some recent attempts of fill in the gap [5,6], there is still a scarcity of experimental data. The validation of numerical results by means of experiments presents a series of challenges that require careful preparation and interpretation of the results.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the composite hydrofoils have the best hydrodynamic performance, showing the potential of a tailored hydroelastic composite hydrofoil. The hydro-elastic behavior of flexible propellers has also been analyzed by Maljaars et al [16]. They compared the results of a boundary element method (BEM) and a Reynolds-averaged-Navier-Stokes (RANS) simulations with the calculation of measured open water diagram and the open water curves.…”
Section: Introductionmentioning
confidence: 99%